Influence of Microstructure on the Ionic Conductivity of Plasma-Sprayed Yttria-Stabilized Zirconia Deposits - Xing, Ya-Zhe; Li, Chang-Jiu; Zhang, Qiang; Li, Cheng-Xin; Yang, Guan-Jun (Journal of the American Ceramic Society, 2008)
Yttria‐stabilized zirconia (YSZ) deposits were prepared by an atmospheric plasma spray (APS) on a stainless‐steel substrate preheated to different temperatures from room temperature to 1100°C. The microstructure of the deposits was characterized from polished and fractured cross sections by scanning electron microscopy (SEM). The ionic conductivity of the deposits was measured using both DC and AC methods, and the relationship between ionic conductivity and microstructure of deposits was examined. SEM observation revealed that the YSZ deposits exhibit different microstructures with different deposition temperatures. With the increase of the deposition temperature, the columnar grain growth across lamellar interfaces was enhanced and subsequently the intersplat bonding ratio in the deposit was improved. The ionic conductivity of YSZ deposits at the direction perpendicular to the deposit surface was significantly increased through the microstructure development on increasing the deposition temperature. However, it was found that the intergrain resistance changed little despite a remarkable change of the deposition temperature. A microstructure model is proposed to correlate the relative conductivity to the mean lamellar interface bonding ratio. The increase in ionic conductivity of the YSZ deposit with the deposition temperature can be attributed to the increase in the lamellar interface bonding ratio.